Language Learning Materials Counteracting Rural Racializations: A Practical Attempt in ELT - Ferney Cruz-Arcila; Sandra Ximena Bonilla-Medina; Vanessa Solano-Cohen (Profile Issues in Teachers' Professional Development)
Colombia is one of the most socioeconomically unequal countries worldwide, with rural regions facing severe poverty, under-resourced schools, precarious economic opportunities, and an unresolved armed conflict. These inequalities are often overlooked in ELT policies and social practices, as rural institutions and educational actors are expected to adhere to English teaching goals that are more aligned with an urban ideal. This misrecognition of the rural socioeconomic and cultural conditions, along with historical racial intersections from colonization, contribute to emerging forms of racialization. Drawing on our research to explore the linkages between L2 education and race, this article examines the racialization of rurality from an ELT angle and introduces a didactic proposal to foster critical consciousness and enact deracialization.